Trade Union Representation and Industrial Relations in Portugal Before, During and Following the Economic and Financial Crises - Stoleroff, A. (Political Institutions and Democracy in Portugal, 2019)
Since 1974, Portuguese trade unions and their confederations have obtained key roles within the institutional model of Portuguese democracy. These concern primarily, but not only, the institutions involved in labour market regulation, namely, collective bargaining and tripartite negotiation. Tellingly, neither the long-term evolution of the model nor the recent crises has directly challenged either of these roles of the unions at a formal level, but they have challenged the substance and efficacy of labour regulation and industrial democracy. It is this potential discrepancy between the formal roles assigned to unions and labour representation and their substantive effects that is the principle object of this chapter. In order to assess the institutional changes that involve labour representation and regulation over time, it traces the relation between neo-liberal influence and policy and economic crisis, exploring the hypothesis that although the institutions “appear to have survived unscathed from an earlier era, the way in which they actually operate has often changed beyond recognition” (Howell 2009: 252–253). To do so, it surveys the transformations of the regulatory institutions throughout democratisation and European integration and in the context of the recent crises, focusing on the protracted decline of unionisation and the crisis of collective bargaining.